Increased immune marker variance in a population of invasive birds - Hanna Prüter (Nature Portfolio, 2020)
Abstract Immunity and parasites have been linked to the success of invasive species. Especially lower parasite burden in invasive populations has been suggested to enable a general downregulation of immune investment (Enemy Release and Evolution of Increased Competitive Ability Hypotheses). Simultaneously, keeping high immune competence towards potentially newly acquired parasites in the invasive range is essential to allow population growth. To investigate the variation of immune effectors of invasive species, we compared the mean and variance of multiple immune effectors in the context of parasite prevalence in an invasive and a native Egyptian goose (Alopochen aegyptiacus) population. Three of ten immune effectors measured showed higher variance in the invasive population. Mean levels were higher in the invasive population for three effectors but lower for eosinophil granulocytes. Parasite prevalence depended on the parasite taxa investigated. We suggest that variation of specific immune effectors, which may be important for invasion success, may lead to higher variance and enable invasive species to reduce the overall physiological cost of immunity while maintaining the ability to efficiently defend against novel parasites encountered.